Position paper of the German Society for Interventional Radiology and Minimally Invasive Therapy (DeGIR) and the German Roentgen Society (DRG) on Structural and Professional Requirements in Interventional Oncology = Positionspapier der Deutschen Gesellschaft für Interventionelle Radiologie und minimal-invasive Therapie (DeGIR) und der Deutschen Röntgengesellschaft (DRG) zu strukturellen und fachlichen Anforderungen in der Interventionelle Onkologie - Isfort, Peter; Sommer, Christof-Matthias; Bruners, Philipp; Maiwald, Bettina; Kühn, Jens-Peter; Radosa, Christoph Georg; Kloeckner, Roman; Freyhardt, Patrick; Franke, Mareike; Moche, Michael; Hoffmann, Ralf-Thorsten; Nikolaou, Konstantin; et al. (RöFo, 2025)
Interventional oncology (IO) employs various techniques to enable minimally invasive, image-guided treatment of tumor diseases with both curative and palliative goals. Additionally, it significantly contributes to managing tumor-related and perioperative complications, offering diverse supportive procedures for patients at all stages of their diseases. The execution of IO procedures places unique demands on the equipment, personnel, and structural organization of radiological clinics, necessitating specific expertise from interventional radiologists. This position paper aims to comprehensively outline the multifaceted aspects of IO and discuss the requisite criteria for hospitals, radiological clinics, and interventional radiologists (IRs). Furthermore, it underscores overarching considerations of quality assurance that clinics and professional societies should prioritize. The requirements for hospitals, radiological clinics, and IRs are varied and demand not only a high level of proficiency in performing IO procedures but also in-depth knowledge of the differential therapy for various tumor diseases. This expertise is essential for effectively serving as clinical partners in the interdisciplinary treatment of oncologic patients. Additionally, a thorough understanding and safe handling of ionizing radiation technologies, along with proficiency in radiation protection methods, which are fundamental aspects of radiological specialist training, is crucial for ensuring the safety of IO procedures for both patients and staff. The Deutsche Gesellschaft für Interventionelle Radiologie und minimal-invasive Therapie (DeGIR) and the Cardiovascular and Interventional Radiological Society of Europe (CIRSE) have long-established dedicated quality management programs, accrediting radiology clinics and certifying IRs. These initiatives aim to uphold the highest standards of care and meet the quality expectations set by politics in healthcare system, particularly in the realm of interventional radiology.